Pentingnya Validitas Tes dalam Meningkatkan Kualitas Evaluasi - Annisa Maryam; Nuraisa Tambak; Husnul Khotimah; Nabila Nabila; Niah Amanda Nur Anisah (Educational Journal, 2026)
Test validity is a crucial aspect of educational evaluation because it determines the extent to which an assessment instrument measures the competencies it is intended to assess. This article aims to examine the importance of test validity in improving the quality of educational evaluation through a literature review approach. Data were collected from various scholarly sources, including books and journal articles, and analyzed descriptively. The findings indicate that test validity plays a significant role in ensuring the accuracy, fairness, and trustworthiness of assessment results. Three main types of validity are identified: content validity, construct validity, and criterion-related validity, each contributing to the alignment of assessment instruments with measurement objectives. Furthermore, the development of valid test instruments requires a systematic process, including the formulation of objectives, preparation of test blueprints, item writing, expert review, pilot testing, and empirical analysis. Instruments with high validity provide evaluation results that can serve as a basis for objective, accurate, and accountable educational decision-making. Therefore, test validity is a fundamental element in enhancing the quality of teaching, learning, and educational evaluation.